KEADILAN PERAN SERTA PEREMPUAN DAN URGENSINYA BAGI PENATAAN RUANG YANG PARTISIPATIF - Indah Nur Shanty Saleh (Gloria Justitia, 2022)
One of the issues of spatial planning strategy is the low participation among women population. The position of women as citizens has not fully received justice to participate towards this issue like men. The purpose of this research is to analyze and explain the importance of women's role in participatory spatial planning. This type of research is normative legal research with secondary data obtained through the literature. The data was analyzed qualitatively, so that it can accurately answered the problem. The research resulted in the following conclusions: Firstly, in the context of Indonesian law, there are legal instruments that guarantee the implementation of participatory justice for everyone, both women and men. However, the reality has not been able to guarantee the realization of justice that participates for women in spatial planning. Secondly, the community participation regulation in spatial planning has not clearly reflect the exact formulation of active community participation. In particular, women roles are still limited as recipients of policies. Third, the urgency of women’s participatory justice in participative spatial planning are based on normative and empirical considerations, namely; women have rights as citizens to enjoy the existence of space, as well as in terms of participation in spatial planning; the field of spatial planning as part of the need to integrate the policies of mainstream gender development, and also the creation of women who have their own wisdom and virtue related to environmental and spatial perspectives that in some point, can not replace by men.